DEVELOPMENT OF CHARACTER EDUCATION MODEL ABILITY OF INFLUENCE ATTITUDE (AIA) - NEURO BASED ON LOCAL WISDOM IN EFFORT SOFT SKILLS IMPROVEMENTS ON SHIPPING VOCATIONAL EDUCATION - Mahadi, Lely Farida; BRubini, Bibin; Retnowati, Rita (Journal of Industrial Engineering & Management Research, 2022)
This study developed new product a character education model for Merchant Marine Vocational education institutions that produced seafarers’ graduates as a generation of young nation ambassadors with high nationalism personal skills. The research subjects were students vocational education institutions that focused on boarding schools or dormitories and those who did not. In fact, the character education management model has contained weaknesses in various aspects, from planning, implementation to evaluation of activities. It departs from the results of analyzing the weakness of the factual model, then reconstructs the conceptual model in order to achieve perfection that accommodates the results of focus group discussions with educating personnel in shipping vocational education institutions. This model has combined various aspects,